Xanthogranulomatous Osteomyelitis Presenting as Swelling in Right Tibia. (17th November 2011) - Kamat, Girish; Gramapurohit, Vandana; Myageri, Aneel; Shettar, Chidendra
Abstract : Xanthogranulomatous osteomyelitis is a very rare form of chronic osteomyelitis which presents like a bone tumor. Three cases of xanthogranulomatous osteomyelitis have been described previously in the literature. We present a case of xanthogranulomatous osteomyelitis occurring in the distal part of tibia. This case presented as swelling in a 13-year-old boy. Simple curettage proved to be curative in the present case.